Novel PANK2 Mutations in Patients With Pantothenate Kinase-Associated Neurodegeneration and the Genotype–Phenotype Correlation - Li, Wen-Bin; Shen, Nan-Xiang; Zhang, Chao; Xie, Huan-Cheng; Li, Zong-Yan; Cao, Li; Chen, Li-Zhi; Zeng, Yuan-jin; Fan, Cui-Xia; Chen, Qian; Shi, Yi-Wu; Song, Xing-Wang (Frontiers in Aging Neuroscience, 2022)
Pantothenate kinase-associated neurodegeneration (PKAN) is a rare genetic disorder caused by mutations in the mitochondrial pantothenate kinase 2 gene (PANK2) and displays an inherited autosomal recessive pattern. In this study, we identified eight PANK2 mutations, including three novel mutations (c.1103A>G/pD368G, c.1696C>G/p. L566V, c.1470delC/p. R490fs494X) in seven unrelated families with PKAN. All patients showed eye-of-the-tiger sign on the magnetic resonance imaging (MRI), six of seven had dystonia, and two of seven had parkinsonism. Bi-allelic mutations of PANK2 decreased PANK2 protein expression and reduced mitochondrial membrane potential in HEK 293T cells. The bi-allelic mutations from patients with early onset PKAN, a severity phenotype, showed decreased mitochondrial membrane potential more than that from late onset patients. We systematically reviewed all reported patients with PKAN with PANK2 mutations. The results indicated that the early onset patients carried a significantly higher frequency of bi-allelic loss-of-function (LoF) mutations compared to late onset patients. In general, patients with LoF mutations showed more severe phenotypes, including earlier onset age and loss of gait. Although there was no significant difference in the frequency of bi-allelic missense mutations between the early onset and late onset patients, we found that patients with missense mutations in the mitochondrial trafficking domain (Transit Peptide/Mitochondrial domain) of PANK2 exhibited the earliest onset age when compared to patients with mutations in the other two domains. Taken together, this study reports three novel mutations and indicates a correlation between the phenotype and mitochondrial dysfunction. This provides new insight for evaluating the clinical severity of patients based on the degree of mitochondrial dysfunction, and suggesting genetic counseling not just generalized identification of mutated PANK2 in clinics.